Isolated pulmonary embolism in a patient with progestin intrauterine device and factor V Leiden - Soluny Jean (Journal of Community Hospital Internal Medicine Perspectives, 2019)
The risk of venous thromboembolism (VTE) in patients using estrogen contraception is well known. However, the association of progestin-only contraception (POC) and the risk of thrombosis is poorly investigated. Few studies on this topic have failed to prove a significant increase in VTE in patients using POC, including patients with a medical condition associated with an increased risk of thrombosis. Therefore, no specific consideration is warranted when using a POC in healthy young females, regardless of an inherited thrombophilia. We present a case of a young woman who has Factor V Leiden (FVL), presenting with an isolated pulmonary embolism (PE) while using a progesterone containing intrauterine device (IUD). The risk of VTE in FVL carriers seems to outweigh the benefit of contraception even when using progestin-only contraception. Therefore, non-hormonal contraception, such as copper IUD, seems to be the only safe alternative for contraception in this population. Further studies are needed to elucidate this observation. Abbreviation: PE: pulmonary embolism; FVL: factor V Leiden; VTE: venous thromboembolism; POC: progestin only contraception; CBC: complete blood count; CMP: complete metabolic panel; ABG: arterial Blood gas; CTPA: CT pulmonary angiography